2018
DOI: 10.3390/vetsci5010013
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Indirect ELISA Based on a Recombinant Chimeric Protein for the Detection of Antibodies against Bovine Babesiosis

Abstract: The current method for Babesia spp. serodiagnosis based on a crude merozoite antigen is a complex and time-consuming procedure. An indirect enzyme-linked immunosorbent assay (iELISA) based on a recombinant multi-antigen of Babesia bovis (rMABbO) was developed for detection of antibodies in bovines suspected of infection with this parasite. The multi-antigen comprises gene fragments of three previously characterized B. bovis antigens: MSA-2c, RAP-1 and the Heat Shock protein 20 that are well-conserved among geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…However, cross reactions were observed when samples from B. bigemina infected cattle were analyzed, thus suggesting that using this assay is an alternative test to detect anti- Babesia sp. antibodies [74]. In general, ELISA has replaced the IFAT as the preferred diagnostic serological test in a diagnostic laboratory, particularly because of the ease and objectivity in interpretation, as well as for the capacity for automatization to process a higher number of samples in a working day.…”
Section: Indirect Immunologic Assaysmentioning
confidence: 99%
“…However, cross reactions were observed when samples from B. bigemina infected cattle were analyzed, thus suggesting that using this assay is an alternative test to detect anti- Babesia sp. antibodies [74]. In general, ELISA has replaced the IFAT as the preferred diagnostic serological test in a diagnostic laboratory, particularly because of the ease and objectivity in interpretation, as well as for the capacity for automatization to process a higher number of samples in a working day.…”
Section: Indirect Immunologic Assaysmentioning
confidence: 99%
“…Various ELISA methods have been used to detect specific antibodies against Babesia species such as B. bovis , B. bigemina , B. divergens , B. caballi , B. canis , B. gibsoni , B. microti , and Babesia sp. Xinjiang ( Bose et al., 1990 ; Kappmeyer et al., 1999 ; Ikadai et al., 2000 ; Fukumoto et al., 2001 ; Boonchit et al., 2002 ; Goff et al., 2003 ; Goff et al., 2006 ; Goff et al., 2008 ; Niu et al., 2016 ; Chung et al., 2017 ; Ortiz et al., 2018 ). Recently, sandwich ELISA techniques based on antigen detection have been developed for the diagnosis of blood parasite infections ( De Arruda et al., 2004 ; Dondorp et al., 2005 ; Chen et al., 2008 ), including B. bovis and B. microti infections ( Montealegre et al., 1987 ; Luo et al., 2012 ; Thekkiniath et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity rates reported in the current study are slightly lower compared with those described in a study using ELISA with a B. bovis chimerical multi-antigen (rMABbo-ELISA), which achieved sensitivity and specificity values of 95.9% and 94.3%, respectively. Such values may be due to the number of antigenic determinants containing the three B. bovis antigens that were used Merozoite Surface Antigen-2c (MSA-2c), Rhoptry-Associated Protein-1 (RAP-1), and heat shock protein 20), which would increase the probability for antibody recognition of B. bovis antigens [ 22 ]. Another study using more than one antigen (rBbSBP-1 + rBbSBP-4) in an indirect ELISA demonstrated the usefulness of this method for the detection of antibodies against B. bovis in cattle compared to results using a single antigen (rBbSBP-1 or rBbSBP-4) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…To avoid nonspecific antibody binding in the tests, all serum samples were subjected to a pre-adsorption process with E. coli cell lysate, as described previously [ 22 , 23 ]. Briefly, 200 µL of E. coli TOP10 (uninduced) cells cultured in LB medium and stored at −80 °C were resuspended in 1 mL of phosphate-buffered saline (PBS) containing 500 µL acid-washed glass beads (Sigma-Aldrich, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%